Keep talking about it: HIV/AIDS-related communication and prior HIV testing in Tanzania, Zimbabwe, South Africa, and Thailand - Ellen Setsuko Hendriksen (2018)
Informal, interpersonal communication within a community about HIV and AIDS, or lack of such communication, may influence community members' uptake of voluntary counseling and testing. Drawing from Noelle-Neumann's spiral of silence theory, this study examined the association between communication about HIV/AIDS and prior HIV testing in communities in Tanzania, Zimbabwe, South Africa, and Thailand. Participants (N = 14,818) in 48 communities across five sites throughout the four countries completed a behavioral survey assessing communication, prior voluntary counseling and testing (VCT) uptake, social norms, stigma, and sexual risk. Site-specific logistic regression models demonstrated that frequent conversations about HIV were significantly associated with prior HIV testing at every site. Odds ratios for each site ranged from 1.885 to 3.085, indicating a roughly doubled or tripled chance of past VCT uptake. Results indicate that verbal communication may be an important mechanism for increasing health behaviors and inclusion in future interventions should be considered. © 2009 Springer Science+Business Media, LLC.